Editorial - English - Mota, Mauricio (REVISTA QUAESTIO IURIS, 2015)
DOI: http://dx.doi.org/10.12957/rqi.2015.15347 The Journal Quaestio Iuris, in this volume 08, number 01, the first 2015 year number, presents an editorial novelty: now our journal will be quarterly, taking into account the new criteria of publishing accordingly to periodicity production flow and number of articles published per year. So now we will have 03 numbers of our magazine a year, each counting with 12 original articles, and thematic dossiers, essays, monographs and reviews always in order to bring to our readership the latest research and studies in the areas of legal theory , Philosophy of Law, Sociology of Law, Dogmatic Legal and History of Law.